Characterization of Bamboo Petung Fiber Reinforced Composites with Environmentally Friendly Enzymes - Raharjo, Rudianto; Widodo, Teguh Dwi; Bintarto, Redi; Alamsyah, Fikrul Akbar (Journal of Mechanical Engineering Science and Technology (JMEST), 2025)
Natural fiber composites are a good choice for many businesses uses because of their better mechanical properties and are friendly environment. Researchers are currently looking into bamboo petung fiber (BPF) and epoxy composites as alternative to synthetic fibers and products made from petroleum. This study's goal is to improve the overall performance of these composites while reducing the need for non-organic materials. This study used the various concentration of bromelain enzyme in BPF to changes the mechanical and physical properties of epoxy composites made from BPF. Composites were characterized the mechanical properties including tensile strength using tensile tester, impact strength using Charpy impact test, bending strength using three point bending methods, and surface morphology observation using scanning electron microscope. This study indicates that BPF composites that have been treated with bromelain enzyme have better mechanical properties. After being treated with bromelain, the BPF composite's tensile strength increase up to 59% with maximum tensile strength of 138.230 MPa, flexural strength increases up to 42% with maximum flexural strength of 135.58 MPa, and impact strength increases up to 64% with maximum impact strength of 4.88 J/m. The bond between the epoxy resin and the BPF makes the composite stronger. These results suggest that combining natural fibers and enzymes can make composite materials that work well and are strong.